2005
DOI: 10.4161/cc.4.11.2152
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 Regulates Gene Expression for Orderly Mitotic Progression

Abstract: Germline mutations of the BRCA1 gene confer an increased risk for breast cancer and ovarian cancer. To study the contribution of BRCA1 to sporadic cancers, which often exhibit reduced BRCA1 expression, we tested the effect of knocking down BRCA1 on gene expression in human prostate (DU-145) and breast (MCF-7) cancer cells. DNA microarray and confirmatory RNA analyses revealed that BRCA1 small interfering (si) RNA caused down-regulation of multiple genes implicated in the mitotic spindle checkpoint (eg., BUB1B,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 38 publications
7
46
0
1
Order By: Relevance
“…38 BRCA1 has been implicated in the spindle assembly checkpoint, such that down-regulation of BRCA1 causes disruption of the mitotic spindle. [39][40][41] This may account for resistance to the microtubule-interfering agent paclitaxel in cells with inhibited endogenous BRCA1 expression. 5,39,42 Therefore, preclinical data implies that patients with low levels of BRCA1 may benefit from single-agent chemotherapy with a platinum drug, whereas those with high levels may benefit from a single-agent taxane.…”
Section: Discussionmentioning
confidence: 99%
“…38 BRCA1 has been implicated in the spindle assembly checkpoint, such that down-regulation of BRCA1 causes disruption of the mitotic spindle. [39][40][41] This may account for resistance to the microtubule-interfering agent paclitaxel in cells with inhibited endogenous BRCA1 expression. 5,39,42 Therefore, preclinical data implies that patients with low levels of BRCA1 may benefit from single-agent chemotherapy with a platinum drug, whereas those with high levels may benefit from a single-agent taxane.…”
Section: Discussionmentioning
confidence: 99%
“…42 This result is not inconsistent with our data, since BRCA1 and p53 are known to physically interact, with BRCA1 acting as a coactivator for p53. 43,44 Interestingly, it was recently demonstrated that BRCA1 also positively regulates the expression of Mad2, 41 another potent inhibitor of the APC/C activity 20 and those of other genes implicated in the mitotic spindle checkpoint, 45 emphasizing BRCA1 requirement in the spindle assembly checkpoint control.…”
Section: Discussionmentioning
confidence: 99%
“…It is not surprising that the EGFRvIII expressing, PTEN-deficient glioblastoma cells also were the most proliferative. Many of the hub genes identified here (ASPM, BUB1, HEK, STK6, NEK2, PTTG1, PRC1, KNSL2, CCNB1, CDC2, and CDC20) also have been shown to be downstream of other key molecular lesions such as BRCA1 in breast cancer (42) or the human papilloma virus proteins E6͞E7 in patients with cervival cancer (for which a ''proliferation cluster'' of 123 genes associated with HPV E6͞E7 in clinical samples strikingly overlapped with the glioblastoma mitosis͞cell cycle module; P ϭ 2.2 ϫ 10 Ϫ16 ) (43). In addition, there was a highly significant overlap with genes that have been shown to be highly overexpressed in high grade breast cancer (P ϭ 3.6 ϫ 10 Ϫ75 ) (44).…”
Section: Gm1600-aspm Sirna Cell Proliferationmentioning
confidence: 99%